Prognostic implication of molecular subtypes and response to neoadjuvant chemotherapy in 760 gastric carcinomas: role of Epstein-Barr virus infection and high- and low-microsatellite instability - Kohlruss, Meike; Blank, Susanne; Schmidt, Thomas; Gaida, Matthias (The journal of pathology: clinical research, 2019)
Epstein-Barr virus positivity (EBV(+)) and high-microsatellite instability (MSI-H) have been identified as molecular subgroups in gastric carcinoma. The aim of our study was to determine the prognostic and predictive relevance of these subgroups in the context of platinum/5-fluorouracil (5-FU) based preoperative chemotherapy (CTx). Additionally, we investigated the clinical relevance of the low-MSI (MSI-L) phenotype. We analysed 760 adenocarcinomas of the stomach or the gastro-oesophageal junction encompassing 143 biopsies before CTx and 617 resected tumours (291 without and 326 after CTx). EBV was determined by PCR and in situ hybridisation for selected cases. MSI was analysed by PCR using five microsatellite markers and classified as MSI-H and MSI-L. Frequencies of EBV(+), MSI-H and MSI-L in the biopsies before CTx were 4.2, 10.5 and 4.9% respectively. EBV(+) or MSI-H did not correlate with response, but MSI-L was associated with better response (p = 0.011). In the resected tumours, frequencies of EBV(+), MSI-H and MSI-L were 3.9, 9.6 and 4.5% respectively. Overall survival (OS) was significantly different in the non-CTx group (p = 0.014). Patients with EBV(+) tumours showed the best OS, followed by MSI-H. MSI-L was significantly associated with worse OS (hazard ratio [HR], 2.21; 95% confidence interval [CI], 1.21-4.04, p = 0.01). In the resected tumours after CTx, MSI-H was also associated with increased OS (HR, 0.54; 95% CI, 0.26-1.09, p = 0.085). In multivariable analysis, molecular classification was an independent prognostic factor in the completely resected (R0) non-CTx group (p = 0.035). In conclusion, MSI-H and EBV(+) are not predictive of response to neoadjuvant platinum/5-FU based CTx, but they are indicative of a good prognosis. In particular, MSI-H indicates a favourable prognosis irrespective of treatment with CTx. MSI-L predicts good response to CTx and its negative prognostic effect for patients treated with surgery alone suggests that MSI-L might help to identify patients with potentially high-benefit from preoperative CTx.